Advances in lignocellulosic feedstocks for bioenergy and bioproducts - Daniel B. Sulis; Nathalie Lavoine; Heike Sederoff; Xiao Jiang; Barbara M. Marques; Kai Lan; Carlos Cofre-Vega; Rodolphe Barrangou; Jack P. Wang (Nature Communications)
Abstract Lignocellulose, an abundant renewable resource, presents a promising alternative for sustainable energy and industrial applications. However, large-scale adoption of lignocellulosic feedstocks faces considerable obstacles, including scalability, bioprocessing efficiency, and resilience to climate change. This Review examines current efforts and future opportunities for leveraging lignocellulosic feedstocks in bio-based energy and products, with a focus on enhancing conversion efficiency and scalability. It also explores emerging biotechnologies such as CRISPR-based genome editing informed by machine learning, aimed at improving feedstock traits and reducing the environmental impact of fossil fuel dependence.